Factors, Routes, and Existing Theories of Technology Commercialization in University: A Conceptual Framework - Dzakiy, Uruqul Nadhif; Simatupang, Togar Mangihut; Prasetio, Eko Agus (STI Policy and Management Journal, 2023)
Technology commercialization in universities which consists of three phases, namely basic research, commercialization feasibility, and commercialization runs non-linearly and goes through licensing and spin-off creation. To achieve commercialization success, there are eight influencing factors, namely academic entrepreneur, role of technology, availability of market, availability of finance, intermediaries' support (i.e. University Technology Transfer Office (UTTO), university's incubator, and proof of concept center), role of collaborative research center, policy support, and regional infrastructure and environment. Meanwhile, the existing management theories that discuss the commercialization of technology in universities mostly use a resource perspective such as Resource-Based View (RBV), resource orchestration theory, and dynamic capabilities with university and spin-offs as unit of analysis. This literature study provides several recommendations for future studies. First, it needs to expand the analysis not limited to licensing and spin-off, and second, it is suggested to develop a resource perspective by enriching what dimensions influence the success of a technology commercialization in universities or provide alternative new management theories in understanding technology commercialization in university.